2016
DOI: 10.1080/08993408.2016.1231469
|View full text |Cite
|
Sign up to set email alerts
|

Gender neutrality improved completion rate for all

Abstract: The purpose of the present study was to investigate if we could improve throughput by refurbishing an online programming course from a gender perspective, while maintaining the focus on preferable learning approaches. The study builds on results from an earlier study that investigated the relationship between approaches to learning and course completion and involves 1067 students that responded to the short version of the Approaches and Study Skills Inventory for Students (ASSIST) in 2010, 2012 and 2013. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This is an open access article distributed under the terms of the Creative Commons CC-BY License (http://creativecommons.org/licenses/by-nc/4.0/). al., 2013; Svedin & Bälter, 2016). Another study showed the short study approach scales to be associated with different information-seeking behaviors in a mixed sample of master's degree students (Heinström, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an open access article distributed under the terms of the Creative Commons CC-BY License (http://creativecommons.org/licenses/by-nc/4.0/). al., 2013; Svedin & Bälter, 2016). Another study showed the short study approach scales to be associated with different information-seeking behaviors in a mixed sample of master's degree students (Heinström, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The short version of the ASSIST has been used in research on students with mixed discipline backgrounds (Heinström, 2005) and on students within fields like medicine (Feeley & Biggerstaff, 2015;Liew, 2015), nursing (Martyn, Terwijn, Kek, & Huijser, 2014), psychology (Prat-Sala & Redford, 2010 and mathematics and computer science (Bälter, Cleveland-Innes, Petterson, Scheja, & Svedin, 2013;Svedin & Bälter, 2016). Heinström (2005) reported that the short scales correlate strongly with the respective full scales (strategic scales: r =0.91; deep and surface scales: r = 0.93).…”
Section: Introductionmentioning
confidence: 99%
“…This is partly due to the selection process, but also due to the fact that computer science is not connoted as a male occupation in many non-Western cultures [30]. For a longer discussion on computer science and gender, see [31].…”
Section: Discussionmentioning
confidence: 99%
“…Since disciplines such as computer sciences are preferred mostly by males, there is a difference in the feeling of efficacy in terms of gender other than the individuals' existing skills and performances. In addition, there is a prejudiced difference had been reported in terms of males and females from an external perspective (Byrne & Lyons, 2001;Svedin & Balter , 2016).…”
Section: Theoretical Background Individual Differences: Social and Comentioning
confidence: 99%